Clinical profile of children with pneumonia admitted at tertiary care hospital, Belgaum: A prospective study - Udaya, K; Murteli, Vijaykumar B; Desai, Arun (Indian Journal of Child Health, 2017)
Background: Acute respiratory infections (ARIs) are a public health problem in India. Timely intervention, correct treatment, and referral service can save many deaths, particularly pneumonia. Objective: This study aimed to study the sociodemographic and clinical profile of children hospitalized with pneumonia and its relation to the duration of stay at a tertiary care center at Belgaum district, Karnataka. Methodology: The study was conducted in Belagavi Institute of Medical Sciences, a referral hospital, during 2013-2015.  Sociodemographic and clinical features of children aged from more than 2 months to 18 years of age were studied. A total of 84 children who met the inclusion criteria for community-acquired pneumonia were studied. The patient population comprises mainly of the low-income group from rural areas, urban slums, referred patients from surrounding rural areas, and private clinics. Results: A total of 84 children were studied, 48 boys and 36 girls. Maximum numbers of children were in low socioeconomic group (43 in upper lower and 37 in lower group) according to modified Kuppuswamy classification. Passive smoking was present in 40.5% of studied and overcrowding was seen in 51% of children studied. 44% of children were breastfed for